Methods of construction of modern house emphasizing on building thermal performance - Priscillina Anak Petrus, @ Petrus Igat. (UNIMAS, 2006)
This project is emphasis on the building thermal performance in modern houses. The temperature on the materials is measured to ensure the material is suitable for the achievement of the comfortability of the occupant in the house. Data analysis made to check the materials temperature external and internal of thematerials surface. Results of the study shows that the materials used are not satisfied the range of thermal comfort. As a conclusion, the understanding of the materials for building construction is essential in choosing a suitable material for constructing the house due to the occupant’s comfortability